ANALISIS KELAYAKAN USAHA HAWK’S DALAM BISNIS SYARIAH - Kurniawan, Rahmat; Roni, Shofyan (Jurnal Pijar, 2023)
This study aims to determine the feasibility of Hawk's business, namely car wash services using applications and including businesses that have never been run before. This research method uses library research. The data obtained is then managed, analyzed in depth. The background for Hawk's is the difficulty the community has in getting services in the form of car washes, even if there are people who have to queue long to get these services so that it takes a long time. Therefore, it is hoped that the existence of the Hawk's application can help the community in solving this problem. In this study there are four aspects to be analyzed including economic and social aspects, aspects of human resources and organizational management, legal and legal aspects and market and marketing aspects. The results of the study show that Hawk's business is feasible to run, because in running this business in the aspect of human resources and management of this business organization, it is not only to achieve profit in the worldly aspect but also from a spiritual perspective it has been fulfilled, namely in terms of capital there is no interest system, from In terms of law and legality, this business is in the form of a firm and has a notarial deed, market and marketing aspects in this business. Furthermore, from the market and marketing aspect, this business uses its own website.